Effective Labor Regulation and Microeconomic Flexibility - Ricardo J. Caballero; Devin N. Cowan; Eduardo M.R.A. Engel; Alejandro Micco (Yale University, Economic Growth Center, 2004)
Microeconomic flexibility, by facilitating the process of creative-destruction, is at the core of economic growth in modern market economies. The main reason for why this process is not infinitely fast is the presence of adjustment costs, some of them technological, others institutional. Chief among the latter is labor market regulation. While few economists would object to such a view, its empirical support is rather weak. In this paper we revisit this hypothesis and find strong evidence for it. We use a new sectoral panel for 60 countries and a methodology suitable for such a panel. We find that job security regulation clearly hampers the creative-destruction process, especially in countries where regulations are likely to be enforced. Moving from the 20th to the 80th percentile in job security, in countries with strong rule of law, cuts the annual speed of adjustment to shocks by a third while shaving off about one percent from annual productivity growth. The same movement has negligible effects in countries with weak rule of law.
Keywords: E24; J23; J63; J64; K00; 330; Microeconomic rigidities; creative-destruction; job security regulation; adjustment costs; rule of law; productivity growth; Arbeitsmarktpolitik; Anpassungskosten; Beschäftigungssicherung; Welt; Schumpeterismus